Manajemen Kinerja Kementerian Sekretariat Negara Dalam Mengelola Pelayanan Informasi Publik - Khaerul Umam; Dimas Ariyoso (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2019)
This present research aims to analyze how the performance management of the Ministry of State Secretary in managing the service of public information. The approach employed in this research is qualitative with descriptive research. To obtain data, the technique used is a literature review through books, journals, articles, and other research. LINDU-DIS is a new breakthrough made by the Deputy Assistant Public Relations to support the implementation of their duties and functions. LINDU-DIS can support providing excellent services to the public who want to obtain information within the Ministry of State Secretary so that it can increase community satisfaction to the Ministry, and in the end, will specifically improve the positive image of the Ministry in the community and generally the government at large. But the thing that needs to be the focus on is that the amount of budget needed in the construction of LINDU-DIS is very large, do not let this budget become ineffective because of the ability of human resources who are not ready to become a barrier in LINDU-DIS operations. Continuous evaluation is also needed to measure the extent to which this program can run and can be replicated by other agencies.Keywords: Public Service, Performance Management, Bureaucracy, Public Information